1999
DOI: 10.1016/s1074-7613(00)80119-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of TLR2 and TLR4 in Recognition of Gram-Negative and Gram-Positive Bacterial Cell Wall Components

Abstract: Toll-like receptor (TLR) 2 and TLR4 are implicated in the recognition of various bacterial cell wall components, such as lipopolysaccharide (LPS). To investigate in vivo roles of TLR2, we generated TLR2-deficient mice. In contrast to LPS unresponsiveness in TLR4-deficient mice, TLR2-deficient mice responded to LPS to the same extent as wild-type mice. TLR2-deficient macrophages were hyporesponsive to several Gram-positive bacterial cell walls as well as Staphylococcus aureus peptidoglycan. TLR4-deficient macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

67
2,298
4
35

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 3,029 publications
(2,404 citation statements)
references
References 45 publications
67
2,298
4
35
Order By: Relevance
“…The bacterial cell envelope components lipopolysaccharide (LPS) and peptidoglycan (PGN) from Gram-negative bacteria have long been known to affect host biology (Cohn and Morse 1960; Hoffmann et al 1999; Kopp and Medzhitov 1999; Takeuchi et al 1999; Medzhitov and Janeway 2000; Kimbrell and Beutler 2001; Koropatnick et al 2004), but neither LPS nor PGN from A. machipongonensis triggered rosette development, alone or in combination (Figure 3A). Instead, we found that A. machipongonensis crude lipid extracts enriched in sphingolipids robustly induced rosette development (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial cell envelope components lipopolysaccharide (LPS) and peptidoglycan (PGN) from Gram-negative bacteria have long been known to affect host biology (Cohn and Morse 1960; Hoffmann et al 1999; Kopp and Medzhitov 1999; Takeuchi et al 1999; Medzhitov and Janeway 2000; Kimbrell and Beutler 2001; Koropatnick et al 2004), but neither LPS nor PGN from A. machipongonensis triggered rosette development, alone or in combination (Figure 3A). Instead, we found that A. machipongonensis crude lipid extracts enriched in sphingolipids robustly induced rosette development (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…TLR2-deficient C57BL/6 mice [33] were backcrossed ten generations to NOD/Caj mice and intercrossed to generate TLR2-deficient homozygous NOD mice [34]. Female C57BL/6 mice were purchased from Charles River Laboratories.…”
Section: Micementioning
confidence: 99%
“…Tlr4 -/- [45], Tlr2 -/- [46], Myd88 -/- [30] and Tirap -/- [29] mice were generated in the C57BL/6 mouse background, and Trif -/- [47] and Tram -/-[48] mice were generated in the C57BL/6/129 mouse background and were made in the BIKEN animal facilities (Osaka, Japan). Lps2, a non-functional codominant allele of Trif, was induced by N-ethyl-N-nitrosourea mutagenesis on a pure C57BL/6 mouse background [49] in the Scripps Institute animal facilities (La Jolla CA).…”
Section: Mouse Strainsmentioning
confidence: 99%